Analisis Faktor Kesulitan Belajar Matematika Siswa Pada Materi Penyajian Data Di MIS TPI Sei Bamban Kec. Batang Serangan Kab. Langkat - Sepnita Nurma Wardhani; Salim Salim; Lailatun Nur Kamalia Siregar (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2023)
This study aims to describe students' difficulties in learning mathematics in mathematics subject data presentation material in class V MIS TPI SEI BAMBAN. The goal is: 1.To find out the difficulties experienced by students in learning mathematics in the material for presenting data at MIS TPI SEI BAMBAN, 2.To find out the factors that cause students to have difficulty learning mathematics in the material for presenting data at MIS TPI SEI BAMBAN 3.For find what efforts were made in overcoming students' learning difficulties in Mathematics in the Data Presentation material at MIS TPI SEI BAMBAN Kec. Batang Serangan Kab. Langkat. This study used qualitative research methods. The techniques used to collect data are observation, interviews, and documentation. The conclusion from the results of this study namely : 1.Types of learning difficulties experienced by students, namely difficulties in understanding formulas, multiplication, division and in data presentation material, namely in line charts. 2.Then the factors that cause student learning difficulties consist of internal factors and external factors. Internal factors include attitudes in students and external factors, namely factors from outside the student's self. 3.Efforts made by the teacher, namely motivating students, learning in a fun way and increasing practice questions.